Effects of honey produced by stingless bee (heterotrigona itama) on spatial memory and learning in female albino mice - Fernandez, Ivanna (2018)
In the 21st century, memory and learning decline is one of the most important health care issues. The use of the effect of honey on memory and learning were investigated since the last decade. To date, sources of honey are limited in tropical countries therefore, stingless bee honey is proposed as an alternative. Stingless bees are found in most subtropical and tropical regions of the world. They are highly eusocial bees and are identified with over 500 species worldwide Scientific research on specific positive effects of stingless bee honey on learning and memory are still lacking. Hence, this study intends to evaluate the effects of stingless honey bee (Heterotrigona itama) honey on memory in female albino mice. Female albino mice aged two to three months were divided into four groups with each group treated with different concentration of honey (750 mg/kg and 2000 mg/kg) for a duration of 7 and 35 days respectively and a control group. Open field exploration test was used to access spatial memory. Following behavioral tests, the mice was sacrificed, and the striatum was harvested for hematoxylin and eosin (H&E) staining. Lastly, genes linked with memory were tested through reverse transcriptase polymerase chain reaction (RT-PCR). The current findings indicated that there are changes in the dose-dependent manner (p≤ 0.05). From behavioral analysis, 2000 mg/kg of stingless honey bee supplementation for seven days showed improvement in the memory and learning of female mice compared to 750 mg/kg of stingless bee honey during total entries to the home base. However, when compared to the total time outside the home based, mice treated for a duration of 35 days spent less time outside the home base as compared to a duration of seven days indicating that mice treated for a longer duration adapted quickly to the environment thus showed a reduce in anxiety as compared to mice treated with stingless bee supplementation for a shorter duration of seven days. Stingless honey bee supplementation did not cause any neurodegenerative changes in the striatum and there was an upregulation of Bdnf, Map2k3 and Itpr1 genes from the brain derived neurotropic (BDNF) pathway. Collectively, the data in this study provides preliminary evidence suggesting that stingless bee honey (Heterotrigona itama) treatment enhances spatial memory and learning performances in female albino mice.